Hydrothermal assisted in situ growth of CoSe onto graphene nanosheets as a nanohybrid positive electrode for asymmetric supercapacitors. Issue 10 (17th January 2017) - Kirubasankar, Balakrishnan; Murugadoss, Vignesh; Angaiah, Subramania
Abstract : Cobalt selenide–graphene (CoSe–G) nanohybrid was successfully synthesised by a one-pot hydrothermal method and used as a positive electrode for asymmetric supercapacitor, which provides an energy density of 45.5 W h kg −1 and a power density of 1.1 kW kg −1 . Abstract : Cobalt selenide–graphene (CoSe–G) nanohybrid was successfully synthesised by a simple and facile one-pot hydrothermal method and used as a positive electrode for an asymmetric supercapacitor. The CoSe–G nanohybrid electrode exhibits a higher specific capacitance of 1037 F g −1 at 5 mV s −1 than CoSe. The electrochemical impedance studies revealed that the graphene in the nanohybrid not only reduced the contact resistance of the electrode but also significantly increases the electrons transport. The good electrochemical performance of CoSe–G is the synergy between CoSe and graphene. In addition, the asymmetric supercapacitor (ASC) was fabricated using CoSe–G and activated carbon as the positive electrode and negative electrode, respectively, and electrospun PVdF membrane containing 6 M KOH as the separator as well as electrolyte. The fabricated ASC delivered an extended operating voltage window of 1.6 V. It also provides a higher energy density of 45.5 W h kg −1 and a power density of 1.1 kW kg −1 and retains 81% of its initial specific capacitance even after 5000 cycles.